2013
DOI: 10.3748/wjg.v19.i37.6193
|View full text |Cite
|
Sign up to set email alerts
|

Acid and non-acid reflux in patients refractory to proton pump inhibitor therapy: Is gastroparesis a factor?

Abstract: The evaluation of patients with a documented history of GP did not show an association between GP and more frequent episodes of non-acid reflux based on MII-pH testing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 22 publications
0
5
0
1
Order By: Relevance
“…3 We observed a striking correlation between gastroparesis symptom severity and increasing taste alterations. In patients with bulimia, it has been suggested that frequent vomiting of at least 3 times per week chronically exposes taste receptors, specifically on the palate, to hydrochloric acid of the stomach, and alters the ability of patients to taste salt, sweet, bitter, and sour solutions.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…3 We observed a striking correlation between gastroparesis symptom severity and increasing taste alterations. In patients with bulimia, it has been suggested that frequent vomiting of at least 3 times per week chronically exposes taste receptors, specifically on the palate, to hydrochloric acid of the stomach, and alters the ability of patients to taste salt, sweet, bitter, and sour solutions.…”
Section: Discussionmentioning
confidence: 74%
“…GERD patients also suffer from numerous upper gastrointestinal (GI) symptoms including heartburn and regurgitation. 3 Patients with both gastroparesis and GERD are advised to manage symptoms by eating less fats and decreasing the frequency and size of meals. 4 From experience in practice, it has been observed that some patients with gastroparesis and with GERD attribute decreased enjoyment when eating to changes in taste and smell function.…”
Section: Introductionmentioning
confidence: 99%
“…One study of 66 patients with refractory GERD who underwent gastric emptying studies found no statistical difference between patients with gastro-paresis and controls with respect to total number or duration of acid and nonacid reflux events. 71 However, a smaller study found that after 8 weeks of PPI treatment, patients with persistent symptoms and EE had more abnormal gastric emptying as compared to patients with persistent EE but no symptoms. 72 A possible association between gastric emptying and refractory GERD was also demonstrated in a small study in which 88% of patients who experienced improvement in gastroparesis symptoms also reported reduced GERD symptoms.…”
Section: Causes Of Refractory Gerdmentioning
confidence: 95%
“…A recent study tried to determine whether an increased number and duration of non-acid reflux events—as measured using the multichannel intraluminal impedance pH (MII-pH)—were linked to GP and found no association between GP and more frequent episodes of non-acid reflux. 8 In contrast, a different study comparing MII-pH measures in patients with and without delayed GE found that patients with delayed GE were more likely to have increased total weakly acidic reflux and prolonged bolus clearance time but similar %pH <4. 24 Forty-three per cent of our patients with delayed GE had abnormal oesophageal acid exposure compared with 38% of our patients with normal GE, and both groups had similar magnitude of pathological acid reflux ( table 1 ).…”
Section: Discussionmentioning
confidence: 94%